Reliability and concurrent validity of a motor skill competence test among 4- to 12-year old children. Issue 14 (18th July 2018) - Hoeboer, Joris; Krijger-Hombergen, Michiel; Savelsbergh, Geert; De Vries, Sanne
ABSTRACT: The purpose of this study was to examine the test-retest reliability, internal consistency and concurrent validity of the Athletic Skills Track (AST). During a regular PE lesson, 930 4- to 12-year old children (448 girls, 482 boys) completed two motor skill competence tests: (1) the Körperkoordination-Test für Kinder (KTK) and (2) an age-related version of the AST (age 4–6 years: AST-1, age 6–9 years: AST-2, and age 9–12 years: AST-3). The test-retest reliability of the AST was high (AST-1: ICC = 0.881 (95% CI: 0.780–0.934); AST-2: ICC = 0.802 (95% CI: 0.717–0.858); and AST-3: ICC = 0.800 (95% CI: 0.669–0.871). The internal consistency, concerning the three age-bands of the AST was above the acceptable level of Cronbach's α > 0.70 (AST-1: α = 0.764; AST-2: α = 0.700; and AST-3: α = 0.763). There was a moderate to high correlation between the time to complete the AST, and the age- and gender-related motor quotients of the KTK (AST-1: r = −0.747, p = 0.01; AST-2: r = −0.646, p = 0.01; and AST-3: r = −0.602, p = 0.01). The Athletic Skills Track is a reliable and valid assessment tool to assess motor skill competence among 4- to 12-year old children in the PE setting.